2017
DOI: 10.1161/jaha.117.006662
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Atrial Fibrillation on Exercise Capacity and Mortality in Heart Failure With Preserved Ejection Fraction: Insights From Cardiopulmonary Stress Testing

Abstract: BackgroundAtrial fibrillation (AF) has been objectively associated with exercise intolerance in patients with heart failure with reduced ejection fraction; however, its impact in patients with heart failure with preserved ejection fraction has not been fully scrutinized.Methods and ResultsWe identified 1744 patients with heart failure and ejection fraction ≥50% referred for cardiopulmonary stress testing at the Cleveland Clinic (Cleveland, OH), 239 of whom had AF. We used inverse probability of treatment weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 34 publications
2
28
0
1
Order By: Relevance
“…Differences between individual groups were around 10% and did not gain statistical significance. Similar observations have been described in the literature [18][19]. There were also studies based on the assessment of physical performance in patients with atrial fibrillation before and after effective electrical cardioversion [20][21].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Differences between individual groups were around 10% and did not gain statistical significance. Similar observations have been described in the literature [18][19]. There were also studies based on the assessment of physical performance in patients with atrial fibrillation before and after effective electrical cardioversion [20][21].…”
Section: Discussionsupporting
confidence: 73%
“…It was found, among other things, that effective and long-term restoration of the sinus rhythm results in a longer distance covered in the test. The beneficial effects of electrical cardioversion on cardiac performance parameters were also confirmed by other haemodynamic, clinical (NYHA), spirometric parameters and also by quality of life [18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 69%
“… 28 29 In fact, reduced exercise tolerance has also been associated with increased mortality in patients with AF. 30 Importantly, previous large-scale prospective longitudinal cohort studies observed changes in CRF concomitantly with mortality outcomes, suggesting that improving VO 2peak through exercise may well reduce mortality. 31 In addition, in healthy elderly men (>65 years of age), muscle strength appears to be directly related to all-cause mortality, 32 even irrespective of muscle mass.…”
Section: Discussionmentioning
confidence: 98%
“…21 Moreover, AF is associated with lower exercise capacity in both HFrEF and HFpEF. 2,3,22 A landmark study of 1,744 patients diagnosed with HFpEF,of whom 239 showed AF, revealed that peak VO 2 was significantly lower -1.8 ml/ kg/min -when AF was present. 22 The authors observed that AF was associated with exercise intolerance, increased mortality and impaired contractile reserve.…”
Section: Physiology Of Exercise Trainingmentioning
confidence: 99%